Implementation of Innovative Strategies Using Special Teaching Materials in Learning Descriptive Text Reading Skills - Yuni Hajar; Yolani Erawati; Sri Ulina Br Sembiring; Tri Lande (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
Innovative strategies are teaching methods that not only combine methods, techniques, and learning approaches but also integrate one learning objective with another. This study aims to describe: 1) This study uses a descriptive method through a quantitative-qualitative approach. The study took place at SD Negeri 104607 Sei Rotan in the odd semester of 2025/2026. The subjects were fifth-grade students of SD Negeri 104607 Sei Rotan. Data on descriptive text reading skills were collected using multiple-choice test instruments; compiled using objective procedures so that valid test requirements were met. Data on descriptive text reading skills learning procedures that apply innovative strategies; were collected using non-test instruments, namely closed observation guidelines. Data on descriptive text reading skills learning procedures that apply innovative strategies were analyzed by determining the suitability between the learning procedures in the lesson plan and the learning procedures that took place in the classroom. Pre-test and post-test data on descriptive text reading skills were analyzed using descriptive statistics, namely mean, percentage, standard deviation, mode, minimum score, and maximum score using the SPSS application. Research results: 1) the results of the pre-test on descriptive text reading skills were in the low category; 2) the learning procedure for descriptive text reading skills that applies innovative strategies is carried out in accordance with the learning procedures contained in the lesson plan; 3) the results of the post-test for descriptive text reading skills are in the high category.